Adjusting dialysis dose (Kt) scaled to Body Surface Area (BSA) could be a more logical approach. - Wei Liu; Zhenguo Qiao; Yan Xu; Qin Zhang; Mengmeng Xie; Chunyuan Ma (PLoS ONE)
The dialysis dose, quantified as Kt, is conventionally scaled to the urea distribution volume (V) to calculate the Kt/V ratio as an indicator of dialysis adequacy. However, the body surface area (BSA) is recognized as a more accurate reflection of metabolic activity compared to V. This study presents evidence supporting the enhanced efficacy of the Kt/BSA ratio as an indicator of hemodialysis adequacy. The study population comprised 211 individuals undergoing hemodialysis, all of whom had Kt/V values determined. Body composition was assessed using bioimpedance techniques, and BSA was calculated employing the DuBois and DuBois formula. The ratio of V/BSA served as the conversion factor to derive Kt/BSA from the standard Kt/V. Participants were categorized by gender, and a comparative analysis was performed on dialysis-related parameters alongside body composition indicators. Concurrently, linear regression analysis was applied to Kt/V and Kt/BSA, as well as to pairs of V and BSA, to elucidate the relationships among these variables. The average Kt/V ratio was 1.50 with a standard deviation of 0.28. The Kt/V ratio was significantly higher in women (P < 0.01). Conversely, the Kt value, when not adjusted for body size, was significantly lower in women (P < 0.01). Upon scaling Kt to BSA to calculate Kt/BSA, the gender difference in dialysis dose adequacy was no longer statistically significant (P = 0.06). Men exhibited a significantly higher mean V/BSA ratio. Additionally, women had a slightly higher mean percentage of fat mass (P < 0.01). In contrast, women had a lower mean percentage of muscle mass (P < 0.01). Our findings suggest that the Kt/V ratio may underestimate the required hemodialysis dose for women. There was no gender difference when Kt scaling to BSA. Consequently, the Kt/BSA ratio, which accounts for body surface area, may play a significant role in more accurately scaling the hemodialysis dose.